2019
DOI: 10.4274/bmb.galenos.2019.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Prognostic Factors in Cerebral Contusions

Abstract: Objective: Cerebral contusion (CC) is vital because it is one of the most common traumatic brain injury (TBI) types and can lead to lifelong physical, cognitive, and psychological disorders. As with all other types of craniocerebral trauma, the correlation of prognosis with specific criteria in CC can provide more effective treatment methods with objective approaches. Method:The results of 105 patients who were hospitalized in the emergency clinic with the diagnosis of CC and whose lesion did not require surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
1
Order By: Relevance
“…Although Neşe Keser, reported that the age had a significant effect on mortality and it increases with increasing age. [14] We couldn't proof such association in our study may be due to limited number of our cases, but it is worthy to mention that in Group B, we found significant differences in the duration of hospital stay by age (P=0.04) with the longest duration in patients <15 years old. Alahmadi H. et al, reported that not all patients with hematoma progression subsequently showed clinical deterioration.…”
Section: Methodscontrasting
confidence: 71%
“…Although Neşe Keser, reported that the age had a significant effect on mortality and it increases with increasing age. [14] We couldn't proof such association in our study may be due to limited number of our cases, but it is worthy to mention that in Group B, we found significant differences in the duration of hospital stay by age (P=0.04) with the longest duration in patients <15 years old. Alahmadi H. et al, reported that not all patients with hematoma progression subsequently showed clinical deterioration.…”
Section: Methodscontrasting
confidence: 71%